Skeletal muscle index/systemic immune-inflammation index (SMI/SII) ratio predicts prognosis in patients with hepatocellular carcinoma - Shu-Xian Li; Wei Huang; Jun-Xiang Li; Tian-Zhi An; Hui-Zhou Li; Chao Hu; Yu-Dong Xiao; Tian-Cheng Wang (World Journal of Surgical Oncology)
Abstract Background Systemic inflammation and skeletal muscle are associated with prognosis in hepatocellular carcinoma (HCC). The prognostic value of a combination of skeletal muscle index (SMI) and systemic immune-inflammation index (SII) remains unclear. The present study aims to investigate the prognostic value of combined SMI and SII in predicting overall survival (OS) for HCCs after liver resection (LR) or transarterial chemoembolization (TACE). Methods This multi-institutional study included three retrospective datasets and one prospective dataset. The SMI/SII was calculated for each cohort. The performance of SMI/SII in predicting recurrence after LR was evaluated in the training cohort, and the optimal cut-off value was calculated. Based on optimal cut-off value, patients were stratified into low and high SMI/SII groups. Cox regression analysis were performed to determine the independent prognostic factors for poor OS. In prospective validation-3 cohort, peripheral blood samples were analyzed for correlation between SMI/SII and distribution of immune cells. Results A total of 1504 patients were included. The AUC of SMI/SII was 0.701. The OS was significantly better in the high SMI/SII group than that in the low SMI/SII group in the training, validation-1, validation-2 cohorts, and combined those three cohorts. Furthermore, low SMI/SII level was an independent prognostic factor for poor OS. Additionally, findings in validation-3 cohort indicated that patients with HCCs and high SMI/SII display anti-tumor attributes in their peripheral blood composition. Conclusion A decreased SMI/SII may be a distinct biomarker of unfavorable prognosis in patients with HCCs, which may be practical to develop personalized treatment strategies for HCC.